Cannabis sativa: uso medicinal e sua contribuição com o tratamento de doenças neurológicas - Nunes, Francisca Monaliza Pereira (Universidade Federal Rural do Semi-Árido, 2019)
The neurobiological knowledge of Cannabis sativa, commonly known as marihuana, has been changing dramatically in the last decade. Surveys about use Cannabidiol (CBD) have been developed around the world. The CBD, the main component of marijuana, until then was on the list of substances banned by the regulator. In order to perform tests for the treatment of different types of symptoms, Anvisa has researched its potential to do the treatment and selection of data on the subject. Known for its morphological and e, active principles this plant has been used for medicinal use since the entrance of Portuguese crown in Brazil. The present work has the same effect of treating cannabis sativa and its effectiveness in combating and treating neurological diseases. The use of CBD in the treatment of diseases, as well as in the treatment of the diseases of the family.
Cannabis sativa: medicinal use and its contribution to the treatment of neurological diseases
Monografia
Keywords: Canabidiol; Princípios ativos.; Tratamento medicinal; Anvisa; Canabidiol; Active principles; Medicinal treatment; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA